Mapping of modern variability of agro‐climatic conditions of the North Caucasus - V. V. Bratkov; S. V. Savinova; P. V. Klyushin; I. A. Kerimov; L. R. Bekmurzaeva (Юг России: экология, развитие)
Aim. Assessment of modern climatic and corresponding cartographic changes in the territory of the North Caucasus for its effective use.Methods. Assessment of the impact of climatic changes and their consequences from the point of view of the conditions of heat and moisture availability of the growing season on the biological productivity of the region, and on this basis the creation of maps of the dynamics of agro‐climatic conditions.Results. The areas of territories with different humidity conditions vary quite significantly over time. Thus, the dry zone of the North Caucasus can almost completely disappear in some years, while other humidity zones are much more stable. The territories where the most arid conditions can be observed have the minimum area for the entire period of time under consideration. Recent changes have led to a reduction in forest‐steppe conditions due to an increase in the area of steppe and dry steppe, which can also be attributed to an improvement in climatic conditions for the production of grain crops.Conclusion. Our research has shown that the territory of the North Caucasus is characterized by a rather significant variability in the conditions of heat and moisture supply during the active vegetation period, which leads to the fact that steppe conditions began to prevail in most of the Western and Central Caucasus, and this favors an increase in grain yields.